Pengaruh Penyesuaian Warna pada Picture Exchange Communication System (PECS) terhadap Kemampuan Working Memory pada Anak Autisme - Irdiansyah, Khairana; Nawangsari, Nur Aini Fardana (Psikodinamika: Jurnal Literasi Psikologi, 2021)
This study aims to determine the effect of colors adjustment on the Picture Exchange Communication System (PECS) on the ability of Working Memory in children with autism. The study was conducted at Autism Training Center (PLA) Sidoarjo and Ceria PAUD Airlangga University with the number of subjects as many as 4 children, with details of 2 children of hyposensitive autism and 2 children hypersensitive autism. The research method used is a Quasi Experiment. The intervention tool during the study was 15 color adjusted PECS images according to Birren's color theory (2010) and Brewster's color theory, created in 1831, under the most hypnotic hypersensitive and hypersensitive conditions according to Mostafa (2008). As for the instrument pretest and posttest researchers use the theory of short-term memory from Atkinson (2014) with the aim to know whether the subject can understand the information with a maximum time of 30 seconds.Based on the results of data analysis using statistical analysis Wilcoxon Signed Rank Test, it was found that there is nosignificant influence between the color on PECS on the ability of working memory of children with autism because the significance value of 0.180 because the number of subjects that are too few is 4 children. However, from the results of pretest posttest graphs and researcher notes, the four subjects experienced a considerable increase in scores. This study focuses on how color affects PECS to improve working memory in children with autism because in previous PECS studies that have been conducted by other researchers, no one has focused on color adjustment in PECS.